The Principle of Integration in Sustainable Development Through the Process of Treaty Interpretation: Addressing the Balance Between Consensual Constraints and Incorporation of Normative Environment - Hagiwara, Kazuki (Université d'Ottawa / University of Ottawa, 2013)
Considering that the concept of sustainable development has a function of normative integration in international law, Article 31(3)(c) provides a legitimate basis of such systemic integration. At the same time, it displays the limitations of the harmonious solution drawn from its application because it works only within the rigid consent-based framework in which the referenced rules should be legal “rules” and should be “applicable in the relations between the parties.” International jurisprudence suggests supplemental elements to overleap the consensual limitations in the application of Article 31(3)(c): a generic term and the object and purpose of the treaty. These text-based and the object-and-purpose-based developmental interpretative techniques enable interpreters to consider legal rules that are not “any relevant rules of international law applicable in the relations between the parties” under Article 31(3)(c).
Keywords: Sustainable development; International law; Vienna Convention on the Law of Treaties; Treaty interpretation; Environmental law; WTO